Enhancement of reflectance of densified vertically aligned carbon nanotube forests - Rana, Masud; M Razib, M Asyraf; Saleh, Tanveer; Asan Gani, Abdul Muthalif (Korean Carbon Society, 2016)
Vertically aligned carbon nanotubes (VACNTs), also known as a carbon nanotube (CNT) forest, are a porous material that is well known for its exceptional optical absorbance property. The reflectance from a VACNT forest has been reported to be as low as 0.045% [1,2]. It is known as the darkest material on Earth. Because of its remarkable material properties, it has various other applications as gas sensors [3], pressure sensors [4], temperature sensors [5], and strain sensors [6]. Recently, various efforts have been made to mechanically manipulate the vertical structure of the nanotubes in the CNT forest and to conduct their optical characterization [7,8]. Optical reflection from bare VACNTs has also been investigated at different wavelengths by Wąsik et al. [9]. Controlled densification by wetting of the CNT forest is another post processing technique that has been reported by other researchers [10]. A densification process is necessary to make the CNT forest useful as a future electronics interconnect [10]. However, no study has been done so far on the optical behavior of CNT forests densified by a wetting process. In this letter, for the first time, we investigate and explain the nature of the optical reflectance of densified VACNTs. Fig. 1 illustrates how the CNT forest is able to absorb most incident light. It was reported elsewhere that VACNT arrays are highly porous [11]. As a result, when incident light enters the bare CNT forest, it goes through several internal reflection-absorption cycles via individual nanotubes and finally makes its way out of the CNT forest as shown in Fig. 1b. Hence, a very low amount of light bounces back (approximately 0.045%) [1,2]. Mathematically, a simple model can be developed to estimate the final amount of light coming out of a CNT forest after several internal reflections; this process is explained by eq (1):